Thermal performance of a heating system combining solar air collector with hollow ventilated interior wall in residential buildings on Tibetan Plateau. (1st September 2019) - Yu, Tao; Liu, Bowan; Lei, Bo; Yuan, Yanping; Bi, Haiquan; Zhang, Zili
Abstract: Solar air heating is very promising in residential buildings on Tibetan Plateau, and effective heat storage is indispensable for continuous heating. Exterior wall is often used for the heat storage, whereas the interior wall is seldom exploited. This paper investigates a heating system combining solar air collector with hollow ventilated interior wall for residential buildings on Tibetan Plateau. A simplified model based on discrete mathematics is established by EnergyPlus and is validated for modeling this system. With this model, a case study is performed to evaluate thermal performances of this system. Moreover, influencing factors of this system are analyzed as well. Results show that compared with the other two typical systems this system increases the minimum indoor air temperature by 6.5 °C and 3.2 °C with night heating need reduced by 79.9% and 60.7%, respectively. For the interior wall material, time constant and thermal inertia are dominant. The optimum window-wall ratio for the south façade is within 0.3–0.4, while the best circulation air flow rate is within 300–500 m³/h. The outdoor air temperature has few influences on the heating performance of this system. Overall, this system is applicable to the heating of residential buildings on Tibet Plateau. Highlights: A simplified method for modeling the SAC-HVIW heating system is proposed. Influences of different factors on the system thermal performance are studied. Thermal performance of this SAC-HIW system is analyzed.